A Comparison of a Conventional Borehole Tool and Distributed Acoustic Sensing at a Dedicated Field Laboratory. Issue 1 (1st December 2018) - Correa, Julia; Dean, Tim; Van Zaanen, Layne; Tertyshnikov, Konstantin; Pevzner, Roman; Bona, Andrej
Abstract : Distributed Acoustic Sensing (DAS) uses standard telecommunication fibre optic cables to detect acoustic and seismic signals. The technique utilises optical time-domain reflectometry; a "light-box" measures the light backscattered from a series of laser pulses emitted into the fibre. As seismic waves impinge on the cable, the fibre is strained, causing variations in the time taken for the backscattered light to travel back up the fibre. The acoustic signal can then be reconstructed by analysing phase differences in the backscattered light. DAS is especially suited for VSP applications, as it offers significant efficiency advantages when compared to conventional borehole acoustic sensors. Conventional VSP surveys usually take an extended period to acquire as the tools need to be placed in multiple positions in the well to record data. With DAS, the complete fibre is a sensor, and thus all levels are acquired simultaneously, reducing the cost considerably. In this work, we compare the results of acquiring a VSP survey using a conventional 3-component geophone tool, a cemented fibre-optic cable, and a suspended fibre-optic cable deployed loosely in the well. The VSP data was acquired at both near and far offset points. Results show that the cemented DAS approached the quality of a conventional geophone VSP survey. The suspended DAS data had smaller SNR, while still clearly acquiring up-going and down-going PP-wave reflections.